2018
DOI: 10.1016/j.cell.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Protein Barcodes Enable High-Dimensional Single-Cell CRISPR Screens

Abstract: Summary CRISPR pools are being widely employed to identify gene functions. However, current technology, which utilizes DNA as barcodes, permits limited phenotyping and bulk-cell resolution. To enable novel screening capabilities, we developed a barcoding system operating at the protein level. We synthesized modules encoding triplet combinations of linear epitopes to generate >100 unique protein barcodes (Pro-Codes). ProCode-expressing vectors were introduced into cells and analyzed by CyTOF mass-cytometry. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 41 publications
(63 reference statements)
2
100
1
Order By: Relevance
“…This was recently highlighted in a novel approach to CRISPR genomics where expression of sgRNAs was coupled with specific protein barcodes, allowing for simultaneous multidimensional phenotypic analysis of several dozen knockouts at a single-cell resolution [48]. In a pooled parallel analysis of gene editing efficiency for ten genes (3–4 sgRNAs per gene), the authors demonstrated that the gene knockout at the protein level was highly variable depending on the sgRNAs used.…”
Section: Guide Rna Efficiency and Specificitymentioning
confidence: 99%
“…This was recently highlighted in a novel approach to CRISPR genomics where expression of sgRNAs was coupled with specific protein barcodes, allowing for simultaneous multidimensional phenotypic analysis of several dozen knockouts at a single-cell resolution [48]. In a pooled parallel analysis of gene editing efficiency for ten genes (3–4 sgRNAs per gene), the authors demonstrated that the gene knockout at the protein level was highly variable depending on the sgRNAs used.…”
Section: Guide Rna Efficiency and Specificitymentioning
confidence: 99%
“…The performance of sgRNAs targeting the same gene can vary dramatically. This was recently highlighted in a novel approach to CRISPR genomics where expression of sgRNAs was coupled with specific protein barcodes, allowing for simultaneous multidimensional phenotypic analysis of several dozens of knockouts at a single cell resolution (Wroblewska et al, 2018). In a pooled parallel analysis of gene editing efficiency for 10 genes (3-4 sgRNAs guide per gene), the authors demonstrated that the gene KO at the protein level was highly variable depending on the sgRNAs used.…”
Section: Guide Rna Efficiency and Specificitymentioning
confidence: 99%
“…Simultaneous with this paper, a method termed Pro-Code that utilises plasma membrane-based epitope barcodes was published. 12 Pro-Code enables highly multiplexed protein-based barcoding of cell clones and was applied in conjunction with single-cell CRISPR screens using flow-based mass cytometry. Although suitable for analysis of clonal dynamics and signalling states at the single cell level in cellular suspensions, such methods are not useful for spatial compartmentalisation and imaging of barcoded clones within complex cellular mixtures or tissues due to close cell-cell membrane contacts resulting in overlapping, indistinguishable cell populations.…”
Section: Introductionmentioning
confidence: 99%